Improving Outcomes of CT-Guided Malignant Lung Lesion Microwave Ablation by Tract Sealing Using Venous Blood Clot - Mačionis, Aurimas; Maziliauskienė, Gertrūda; Dubeikaitė, Rūta; Vajauskas, Donatas; Adukauskienė, Dalia; Nedzelskienė, Irena; Žemaitis, Marius (Diagnostics (Basel), 2024)
Background: Complications, particularly pneumothorax, are common following lung interventions and occasionally necessitate further examinations, extend hospital stays, increase treatment costs, and result in long-term health impairment or even death. A few lung intervention tract sealants have been explored to reduce procedure-related complications. Objectives: The primary objective of this prospective non-randomized study was to assess the complication rates and risk factors for computed tomography-guided lung microwave ablation (MWA) with autologous blood clot as a tract sealant. Methods: Twenty-one patients underwent a total of 26 MWA sessions for lung malignancy followed by injection of the patient’s clotted venous blood into the ablation tract while retracting the coaxial needle. Ablation tract sealing was successful in all MWA sessions. Results: Pneumothorax was the only complication observed in five (19.2%) sessions, with one patient (3.8%) requiring chest tube insertion. The male sex was a statistically significant risk factor for pneumothorax (p = 0.042), and patients with lung emphysema had almost fivefold higher odds of developing pneumothorax (OR 4.8; 95% CI, 0.617–37.351; p = 0.281). Conclusions: This study concludes that pneumothorax is the primary complication following lung MWA, and the male sex is a risk factor. Ablation tract sealing with autologous venous blood is a straightforward and inexpensive technique that can reduce the incidence of procedure-related pneumothorax.